Personal resources and turnover intention among private sector employees: Does work engagement still matter? - Hardaningtyas, Ratna Tri (University of Islam Malang, 2020)
Work engagement has emerged as a core element of talent management to acquire and retain high-performing employees in the labor market and a potential bright spot for business success. Due to the aforementioned positive influences and benefits of improving employees' work engagement, many organizations put more effort towards enhancing and maintaining levels of work engagement as their top priority for an effective human resource system. This study aimed to investigate the mediating effects of employees' work engagement in the relationships between their personal resources (self-efficacy, organizationalbased self-esteem, and optimism) and turnover intention. A total of 119 survey responses collected by convenience sampling and analyzed by using structural equation modeling (SEM). This study concluded that there is a positive relationship between self-efficacy, organizationalbased self-esteem, optimism, and work engagement. The mediation role of work engagement in the relationship between self-efficacy, organizational-based self-esteem, optimism, and turnover intention proves significantly in this study. Interestingly, this study found that there is a positive relationship of self-efficacy on turnover intention which means that the higher level of self-efficacy does not indicate the lower turnover intention. Employees with a high level of self-efficacy believe that they are giving too much to their organization Therefore, they eventually negotiated more for higher salaries while at the same time seeing more alternative jobs/organizations offers in case they are not appreciated enough for what they do for organizations.